Neurosyphilis with concomitant cryptococcal meningitis in a patient with AIDS after COVID-19: a case report - Qi Wang; Yunfei Pan (Journal of Infection in Developing Countries)
Background: The common infection agents causing meningitis in patients with human immunodeficiency virus (HIV) include Cryptococcus neoformans and Treponema pallidum. Furthermore, there is an elevated risk of meningitis in patients with HIV concomitantly infected with SARS-CoV-2.